Zeolite and Aluminium catalytic thermolysis of HDPE: A study on the effect of temperature - SangeetaH. Deshpande,G.L.Agawane, N.V. Iyer,J.A. Kher3, *, (International Journal of Advanced Science and Technology, 2020)
Degradation of plastic polymers by thermal ways has attracted attention of researchers worldwide since these plastic materials can be converted into important chemicals and oil products. In this paper, we report, conversion of high-density polyethylene (HDPE) into various petroleum fractions by catalytic pyrolysis. A laboratory designed, simple and low cost experimental set up was used in this work. Freshly obtained HDPE was used to convert into various fractions and the temperature varied from 100°C to 300 °Cwith increment of 50 °C. Two different sets of experiment were prepared. In set one only Zeolite catalyst was used while in second set Zeolite along with Alumina was used. The Gas Chromatography-Mass Spectrometry (GCMS) chemical analysis of the HDPE pyrolytic oil showed the presence of various functional groups like alkanes, alkenes, alcohols and phenyl ring substitution bands.The detailed GCMS analysis showed presence of cyclo-octane, cyclo-decane, 1 Decene,1, 14 Tetradecanediol in presence of Zeolite and Alumina catalyst. While in the presence of only Zeolite catalyst fractions like 1 Octadecyne, 1 Pentadecene, Nonadecane were oobtained.From the studies, it was revealed that the chemical properties of the obtained thermolytic oil were close to mixture of petroleum commodities.